2017
DOI: 10.1016/j.carbpol.2017.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physicochemical properties of granular starches after treatment with debranching enzyme

Abstract: Please cite this article as: Li, Ping., He, Xiaowei., Dhital, Sushil., Zhang, Bin., & Huang, Qiang., Structural and physicochemical properties of granular starches after treatment with debranching enzyme.Carbohydrate Polymers http://dx.doi.org/10. 1016/j.carbpol.2017.04.036 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Figure shows the micrographs for different degrees of modification (native PS…PUL‐40). Native PS was found to have a smooth and rigid granule surfaces, which is basically consistent with the finding reported by Li et al The micrographs in Figure (A–H) illustrate that the surface of starch granules was slightly affected by the enzymatic treatment and probably the subsequent preparation steps. However, the specificity of the damage increased with increasing enzyme dosage by trend.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Figure shows the micrographs for different degrees of modification (native PS…PUL‐40). Native PS was found to have a smooth and rigid granule surfaces, which is basically consistent with the finding reported by Li et al The micrographs in Figure (A–H) illustrate that the surface of starch granules was slightly affected by the enzymatic treatment and probably the subsequent preparation steps. However, the specificity of the damage increased with increasing enzyme dosage by trend.…”
Section: Resultssupporting
confidence: 90%
“…They proved significantly affected T c and Δ T gel by the enzymatic degradation, while T o and T p did not change. In contrast, Li et al detected increasing gelatinization temperatures with increasing degree of hydrolysis by PUL.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Among these modifications, enzymatic modification is normally used for improving the quality of food starches. Several studies have reported that the starch debranched using pullulanase greatly improve the formation of resistant starch and the characteristics of starch . In addition, physical modification of starch reduces its melting temperature, viscosity, and swelling power and increases its solubility .…”
Section: Introductionmentioning
confidence: 99%